Effects of Three Different Modes of Resistance Training on Appetite Hormones in Males With Obesity - Ataeinosrat, Ali; Haghighi, Marjan Mosalman; Abednatanzi, Hossein; Soltani, Mohammad; Ghanbari-Niaki, Abbass; Nouri-Habashi, Akbar; Amani-Shalamzari, Sadegh; Mossayebi, Ali; Khademosharie, Mitra; Johnson, Kelly E.; VanDusseldorp, Trisha A.; Saeidi, Ayoub; et al. (Frontiers in Physiology, 2022)
Purpose: This study explored the effect of three different modes of resistance training on appetite hormones (leptin, ghrelin, cholecystokinin [CCK], glucagon-like peptide-1 [GLP-1], and peptide tyrosine-tyrosine [PYY]), cardiometabolic and anthropometric measures in males with obesity. Methods: Forty-four males with obesity (age: 27.5 ± 9.4 yrs; mean weight: 93.2 ± 2.2 kg, body mass index [BMI]: 32.9 ± 1.2 kg/m2) were randomized to traditional resistance training (TRT, n=11), circuit resistance training (CRT, n=11), interval resistance training (IRT, n=11) or control (C, n=11) groups. All resistance training groups received 50 min of supervised training per session, three days per week, for 12 weeks. Measurements were taken at baseline and after 12 weeks of training. Results: Plasma levels of leptin, ghrelin, CCK, and PYY decreased significantly in all three different modalities of resistance training groups when compared to the control group (p<0.05). GLP-1 increased significantly in both CRT and IRT groups compared to TRT and C groups (p<0.05). Glucose-dependent insulinotropic polypeptide (GIP) decreased significantly in CRT and IRT groups compared to the C group (p<0.05). Adiponectin levels increased significantly in all resistance training groups compared to the C group (p<0.05). Conclusion: Overall, CRT and IRT protocols had the greatest impact on appetite hormones compared to individuals who engaged in TRT or did not exercise (C).